2018
DOI: 10.1002/psc.3144
|View full text |Cite
|
Sign up to set email alerts
|

Improved mitochondrial targeting effect of HPMA copolymer by SS20 peptide mediation and nonendocytosis pathway

Abstract: Mitochondrion plays an important role in executing cell programmed death pathway.Therefore, drugs designed to target mitochondria are supposed to make superior contributions to cancer therapy. However, the problem that drugs or drug delivery systems being sequestrated in endosomes/lysosomes needs to be solved for effective drug delivery. Here, mitochondrial targeting and nonendocytic cell entry peptide SS20 modified HPMA copolymer (P-FITC-SS20) was synthesized. With SS20 peptide modification, the uptake behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Mitochondrial dysfunction triggers mitochondria-associated intrinsic apoptosis. , XPO1 controls the nucleo-cytoplasmic trafficking of several key growth regulatory and tumor suppressor proteins. As a result, a selective inhibitor of nuclear export compound, KPT-330, was reported to have the ability to cause cell cycle arrest and apoptosis. ,, Our results showed that both KPT NPs and TL NPs displayed proapoptosis effects; what is more, their combination induced the strongest apoptosis (Figure F) as expected.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial dysfunction triggers mitochondria-associated intrinsic apoptosis. , XPO1 controls the nucleo-cytoplasmic trafficking of several key growth regulatory and tumor suppressor proteins. As a result, a selective inhibitor of nuclear export compound, KPT-330, was reported to have the ability to cause cell cycle arrest and apoptosis. ,, Our results showed that both KPT NPs and TL NPs displayed proapoptosis effects; what is more, their combination induced the strongest apoptosis (Figure F) as expected.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve mitochondria targeting delivery, mitochondria-targeting signal peptides and lipophilic cations (e.g., triphenylphosphonium, dequalinium) have been used. However, as some mitochondria targeting groups do not have a significant tumor cell targeting ability or cannot enhance cellular uptake of drugs, the simultaneous use of a cell targeting peptide or cell penetrating peptide as well as a mitochondria targeting ligand in drug delivery systems was developed . Another strategy is to use a ligand which is able to increase both cellular uptake and mitochondria targeting .…”
Section: Introductionmentioning
confidence: 99%